Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jns.2019.116516
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacodynamics of a novel recombinant botulinum toxin E (rBoNT-E): Results of a phase 1 study in healthy male subjects compared with abobotulinumtoxinA (Dysport®)

Abstract: Naturally occurring botulinum toxin (BoNT) serotypes have different pharmacological features of therapeutic and aesthetic interest. This phase 1, double-blind, placebo-controlled study (EudraCT: 2016-002609-20) assessed safety, tolerability and pharmacodynamics (PD) of the first recombinant BoNT serotype E (rBoNT-E) versus abobotulinumtoxinA (Dysport®), administered to extensor digitorum brevis (EDB) of healthy males. Subjects were randomised 3:1 (n = 28) to single ascending rBoNT-E (0.04-3.6 ng) doses or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
1
21
1
1
Order By: Relevance
“…This does not t with previous experiments done on primary rodent cells [31] that indicated that BoNT/A was 30 times more potent than BoNT/E. But our ndings match with the observations from the rst clinical trial in human (phase one study) in which it was shown that BoNT/E potency is at least equivalent or even greater compare to toxin A [24]. These observations underline the translational value of a human cellular model.…”
Section: Discussionsupporting
confidence: 56%
“…This does not t with previous experiments done on primary rodent cells [31] that indicated that BoNT/A was 30 times more potent than BoNT/E. But our ndings match with the observations from the rst clinical trial in human (phase one study) in which it was shown that BoNT/E potency is at least equivalent or even greater compare to toxin A [24]. These observations underline the translational value of a human cellular model.…”
Section: Discussionsupporting
confidence: 56%
“…In particular, BoNT/A is known for its long-lasting clinical response (3–4 months). More recently, serotype E has been investigated in clinical trials [ 11 , 12 ], since its distinct pharmacological profile may represent an interesting therapeutic alternative for applications where a faster onset and shorter duration of effect is beneficial [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the rBoNT-E group, time to onset ranged from 1-2 days compared to 1-7 days for the AboBoNT-A group. The maximum effect for the rBoNT-E group was 1 week and the effect lasted from 10 to 50 days depending on the dose injected [59]. This shorter acting toxin may be useful given the rapid onset of action and shortened duration of effects in novel clinical applications and approaches to dystonia management.…”
Section: Other Toxins Not Fda-approved For Dystoniamentioning
confidence: 99%